Desain dan implementasi pengukuran parameter lingkungan dengan Raspberry Pi sebagai node - Agvion Virsaw; Isnain Gunadi; Kusworo Adi (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
Environment is a system that greatly affects the growth and development of organisms. In this earthly life, the environmental factors such as temperature, humidity and light intensity is an element which greatly affect humans, animals and plants to be able to adapt to its environment. Pollutants in the environment will be different in a place where others because of their conditions of temperature, humidity and lighting that will bring great influence in the spread of pollution, both in the local scale (the environment) or regional scale (environmental and vicinity). The effects of air pollution is the result of adverse impact on the environment, human health, and many living things on earth. Air pollution is a disorder that most complaints by the people. By making measurements of environmental parameters monitoring tool with LDR sensor for measuring changes in light, and DHT11 to measure changes in temperature and humidity that will be processed by the Raspberry Pi which is then displayed on a 16x2 LCD interface and stored in the database. Expected to monitor environmental parameters in real time. Some of the variables resulting from the environmental parameter measurement system with Raspberry Pi as a node such as temperature, humidity, and light intensity in the environment. The results of the data obtained by the sensor readings performed by the Raspberry Pi has a fairly good accuracy of ± C for temperature, ± 5% RH for humidity, and ± 4,3 Lux intensity. The result shows that the system is running well. Keyword : LDR Sensor, DHT11, LCD 16x2, Raspberry Pi, Database